надо решить 12 и 13 ) ) ото туплю(

надо решить 12 и 13 ) ) ото туплю(

  • 12. ((a^2-ab-b^2+ab)/ab) * b/(a-b)= ((a^2-b^2)/ab) * b/(a-b) = (a^2-b^2)/a(a-b) =

    = (a+b)(a-b)/a(a-b) = (a+b)/a

    Ответ: (a+b)/a

    13. ((ax+x^2-ax)/a(x-a)) * (x-a)/x = x^2/(a(x-a)) * (x-a)/x = x/a

    Ответ: x/a

  • 12)((a-b)/b-(b-a)/a)*b/(a-b)=((a^2-ab-b^2+ab)/ab)*b/(a-b)=(a^2-b^2)/ab*b/(a-b)=(a-b)(a+b)/ab*b/(a-b)=(a+b)/a

    13)(x/(x-a)+x/a)/x/(x-a)=((ax+x^2-ax)/a(x-a))/x/(x-a)=x^2/(a(x-a))/x/(x-a)=x^2/a(x-a)*(x-a)/x=x/a